Graphene-modified epoxy resin-based encapsulating material and preparation method thereof
By modifying graphene and aluminum nitride, the problem of agglomeration of thermally conductive fillers in epoxy resin was solved, and the thermal conductivity, insulation and mechanical properties of epoxy resin-based encapsulation materials were improved.
Patent Information
- Application Number
- CN202510594109.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2025-05-09
- Publication Date
- 2025-11-28
- Estimated Expiration
- 2045-05-09
AI Technical Summary
In the prior art, thermally conductive fillers tend to agglomerate in epoxy resin, leading to difficulties in mixing and poor interfacial bonding, which affects the thermal conductivity, insulation and mechanical properties of epoxy molding compounds.
By oxidizing graphene to introduce oxygen-containing functional groups and dicarboxyl groups, the bonding force between graphene and epoxy resin is improved. The surface of aluminum nitride is then treated with plasma oxidation to increase its interfacial bonding force with epoxy resin, thus preparing a modified epoxy resin-based encapsulation material. Plasma oxidation treatment of the aluminum nitride surface further enhances its insulation performance with the epoxy resin-based encapsulation material.
This method achieves uniform dispersion of graphene in epoxy resin, improves thermal conductivity and insulation properties, and synergistically enhances the mechanical properties of epoxy resin-based encapsulation materials.
Smart Images

Figure BDA0005394023920000181 
Figure BDA0005394023920000191 
Figure BDA0005394023920000192
Abstract
Description
TECHNICAL FIELD
[0001] The application belongs to the technical field of epoxy encapsulation material preparation in electronic packaging, and particularly relates to a graphene modified epoxy resin based packaging material and a preparation method thereof. BACKGROUND
[0002] Epoxy encapsulation material (EMC) is a core material in the field of semiconductor packaging, mainly used for protecting chips from the influence of external environment (water vapor, temperature, mechanical impact, etc.), and realizing the composite functions of heat conduction, insulation, voltage resistance, etc. With the development of semiconductor technology towards miniaturization, high integration and high performance, the performance requirements of epoxy encapsulation material are continuously upgraded, becoming one of the key materials for promoting the progress of electronic packaging technology. Epoxy encapsulation material is mainly composed of epoxy resin, curing agent and heat-conducting filler. The main role of the heat-conducting filler is to improve the thermal conductivity of the epoxy resin, and it is one of the core components of the epoxy encapsulation material. At present, the heat-conducting filler is mainly divided into inorganic non-metallic and carbon materials. Inorganic non-metallic fillers include aluminum oxide, aluminum nitride and boron nitride, etc., and carbon materials include graphite, carbon fiber, carbon nanotube and graphene, etc. Although the heat-conducting filler can effectively improve the thermal conductivity of the epoxy resin material, a high filler amount is often required to obtain good thermal conductivity, and a high filler amount often leads to the easy aggregation of the heat-conducting filler, making it difficult to mix with the epoxy resin, and the interface between them is poorly compatible, resulting in a large number of pore defects in the prepared epoxy encapsulation material, thereby seriously reducing the insulation performance and mechanical performance of the epoxy encapsulation material. Therefore, improving the dispersion performance of the heat-conducting filler and the compatibility between the heat-conducting filler and the epoxy resin play an important role in improving the thermal conductivity, insulation and mechanical performance of the epoxy encapsulation material.
[0003] Patent CN117736549A discloses a preparation method of a high-thermal-conductivity epoxy resin composite. The invention mixes prismatic aluminum oxide, flaky boron nitride, nano-silicon nitride, silane coupling agent and water to obtain modified inorganic powder; mixes epoxy resin and colorant, stirs and heats, then adds the modified inorganic powder in batches and degasses, and then adds acid anhydride curing agent and curing accelerator, and heats to cure, to obtain a high-thermal-conductivity epoxy resin composite. The acid anhydride curing agent in the invention can quickly realize the curing of the epoxy resin at a lower temperature under the action of the curing accelerator, and the combination of different types of particles with specific particle size and morphology can significantly improve the thermal conductivity of the epoxy resin composite at a lower addition amount.
[0004] Patent CN110804280A discloses a preparation method of a super-high-thermal-conductivity epoxy resin / graphene composite material. The invention first attaches PEG molecules to the surface of graphene to prepare a PEG / graphene composite material. Since PEG has good compatibility with epoxy resin, the presence of PEG can greatly increase the addition amount of graphene while maintaining excellent mechanical properties and thermal conductivity.
[0005] Patent CN118496622A discloses a high-insulation filling type high-thermal-conductivity epoxy resin composite material, a preparation method and application thereof, the invention uses epoxy resin-based boron nitride and aluminum oxide as the matrix, uses high-insulation performance polyimide as the filling item, blends the matrix and the filling item through a vacuum stirring box, and obtains the high-insulation epoxy resin-based thermal-conductivity composite material through high-temperature curing by a flat curing instrument.
[0006] Graphene is a kind of carbon material with high thermal conductivity, but due to its own electrical conductivity, if the addition is too high, it is not suitable for the requirement of insulation performance of epoxy resin composite material in some fields, therefore, it is of great significance to study the graphene to improve the thermal conductivity of epoxy resin material while realizing good insulation performance. SUMMARY
[0007] According to the deficiencies of the prior art, the modified epoxy resin material, the curing agent, the curing accelerator, the benzoyl peroxide and the modified thermal conductive filler are mixed and dispersed to form a dispersion material, and the dispersion material is subjected to high-temperature curing after being subjected to defoaming treatment to obtain an epoxy resin-based packaging material, so as to solve the technical problems in the background art. Specifically, the technical scheme of the present application includes the following contents:
[0008] One of the purposes of the present application is to provide a graphene-modified epoxy resin-based packaging material and a preparation method thereof, the preparation method comprising the following steps:
[0009] The modified epoxy resin material, the curing agent, the curing accelerator, the benzoyl peroxide and the modified thermal conductive filler are mixed and dispersed in a weight ratio of 20-30:16-19:1-2:0.4-0.6:25-28 to form a dispersion material, the dispersion material is poured into a mold coated with a release agent, and is subjected to vacuum defoaming treatment at 45 DEG C for 30-35 min, and then is sequentially subjected to curing at 110 DEG C for 1-2 h and curing at 130 DEG C for 2-3 h to obtain an epoxy resin-based packaging material.
[0010] Further, the preparation method of the modified epoxy resin material comprises the following steps:
[0011] The graphene powder, concentrated sulfuric acid and potassium permanganate are mixed and reacted at 4 DEG C-6 DEG C for 3 h-4 h, and then the temperature is increased to 60 DEG C-70 DEG C for reaction for 2 h-3 h to obtain graphene oxide;
[0012] The graphene oxide, oleic acid and p-toluenesulfonic acid are mixed and heated to 80 DEG C-90 DEG C for reaction for 4 h-5 h to obtain modified graphene oxide;
[0013] The modified graphene oxide, epoxy resin and tetrabutylammonium bromide are mixed and stirred and heated to 100 DEG C-110 DEG C for reaction for 6 h-8 h to obtain a modified epoxy resin material.
[0014] Further, the particle size of the graphene powder is 15-20 mu m.
[0015] Further, the mass fraction of the concentrated sulfuric acid is 98%.
[0016] Further, the weight ratio of the graphene powder, the concentrated sulfuric acid and the potassium permanganate is 1:42-48:9-12.
[0017] Further, the olefinic acid includes maleic acid, and the olefinic acid structure needs to contain a carbon-carbon double bond and not less than two carboxyl groups, the carbon-carbon double bond is used for subsequent polymerization by an initiator to introduce the modified heat-conductive filler into the epoxy resin to realize heat-conductivity modification, and the carboxyl group is used for condensation with the hydroxyl group on the surface of the graphene oxide on one hand, and ring-opening esterification of the carboxyl group and the epoxy resin under the catalysis of tetrabutylammonium bromide on the other hand, so as to introduce the graphene oxide into the epoxy resin to realize heat-conductivity modification.
[0018] Further, the weight ratio of the graphene oxide, the maleic acid and the p-toluenesulfonic acid is 1:3-5:0.03-0.12.
[0019] Further, the epoxy resin includes bisphenol A type epoxy resin E-44 or bisphenol A type epoxy resin E-51.
[0020] Further, the weight ratio of the modified graphene oxide, the epoxy resin and tetrabutylammonium bromide is 1:6-12:0.1-0.2.
[0021] Further, the curing agent includes isophorone diamine or tetrahydrophthalic anhydride.
[0022] Further, the curing accelerator includes triethylamine, triethanolamine or 2-methylimidazole.
[0023] Further, the preparation method of the modified heat-conductive filler includes the following steps:
[0024] The aluminum nitride is oxidized by plasma to obtain modified aluminum nitride;
[0025] The modified aluminum nitride, the unsaturated silane coupling agent, the deionized water and the anhydrous ethanol are mixed to form a dispersion liquid, the pH of the dispersion liquid is adjusted to 4-4.5 and the dispersion liquid is heated to 70-80 DEG C for 60-70 min to obtain the modified heat-conductive filler.
[0026] Further, the particle size of the aluminum nitride is 30-40 mu m.
[0027] Further, the conditions of the plasma oxidation include that the plasma gas source is oxygen, the gas flow is 100-150 mL / min, the processing power is 200-300 W and the processing time is 60-90 s.
[0028] Further, the unsaturated silane coupling agent includes vinyl trimethoxysilane or vinyl triethoxysilane, and the unsaturated silane coupling agent needs to have a carbon-carbon double bond for subsequent introduction of the modified heat-conductive filler into the epoxy resin through polymerization to improve the heat-conductive performance.
[0029] Further, the weight ratio of the modified aluminum nitride: unsaturated silane coupling agent: deionized water: anhydrous ethanol is 1: 0.4-0.7: 3-6: 10-15.
[0030] Further, the release agent includes microcrystalline paraffin wax.
[0031] The second object of the present application provides a preparation method of the graphene-modified epoxy resin-based packaging material.
[0032] Compared with the prior art, the present application has the following advantages:
[0033] The present application first uses graphene with high heat-conductive performance as one of the materials for improving the heat-conductive performance of the epoxy resin material, and the graphene powder with a specific particle size is modified by oxidation. The oxidation modification not only enables the surface to obtain oxygen-containing functional groups carboxyl, but also enables the esterification reaction with maleic acid with double carboxyl to obtain modified graphene oxide, and then realizes the surface modification of the graphene to realize the dispersion of the graphene. The oxidation modification can enable the carbon atoms in the graphene structure to form a hexagonal honeycomb structure by sp 2 The hexagonal honeycomb structure is destroyed by the oxygen-containing functional groups to weaken the conductivity. The modified graphene oxide is obtained by the condensation reaction of the carboxyl and the epoxy resin to obtain the modified epoxy resin material, which improves the bonding force between the graphene and the surface of the epoxy resin. Then, the aluminum nitride with a specific particle size with good insulation performance and heat-conductive performance is used as the heat-conductive filler, the surface is obtained by plasma oxidation to obtain oxygen-containing groups such as hydroxyl, and then the condensation coupling is carried out with the unsaturated silane coupling agent to obtain the modified heat-conductive filler. On the one hand, the interface bonding force between the aluminum nitride and the epoxy resin is improved, and on the other hand, the condensation polymerization is carried out with the modified epoxy resin material to obtain the epoxy resin-based packaging material, which can improve the heat-conductive performance of the epoxy resin-based packaging material caused by the oxidation and esterification modification of the graphene, and the insulation performance of the aluminum nitride is further improved to improve the insulation performance of the prepared epoxy resin-based packaging material. DETAILED DESCRIPTION
[0034] The technical solutions of the present application will be described clearly and completely by the embodiments of the present application. Obviously, the described embodiments are only a part of the embodiments of the present application, but not all the embodiments. Based on the embodiments in the present application, all other embodiments obtained by those skilled in the art without creative labor are within the scope of protection of the present application.
[0035] Unless otherwise indicated, the starting materials and reagents used in the present application below are commercially available or can be prepared by known methods.
[0036] Preparation Example 1:
[0037] The preparation method of the modified epoxy resin material specifically includes the following processes:
[0038] Take 3 parts by weight of graphene powder with a particle size of 15 μm into a beaker, and then slowly pour 126 parts by weight of concentrated sulfuric acid with a mass fraction of 98% into the beaker to mix with the graphene powder. Then, place it in a low-temperature environment of 4°C, and then slowly add 27 parts by weight of potassium permanganate into the above mixed system. Stir at a speed of 200 r / min and react in a low-temperature environment of 4°C for 3 h. After the low-temperature reaction is completed, take it out and continue to stir and react at a temperature environment of 60°C for 2 h. After the reaction is completed, cool it to room temperature, add 5% mass fraction of hydrogen peroxide to mix and stir until the system presents yellow color. Collect the particles by filtration, first wash with dilute hydrochloric acid, then wash with deionized water until the pH of the leaching water is neutral, and then dry to obtain graphene oxide. Take 2 parts by weight of graphene oxide and 6 parts by weight of maleic acid together into anhydrous acetone, treat for 10 min under a ultrasonic power of 300 W, and then add 0.06 parts by weight of p-toluenesulfonic acid to mix and stir, and then heat to 80°C for timed reaction for 4 h. After the reaction is completed, cool it to room temperature, and then filter to obtain a filter cake. Wash the filter cake repeatedly with deionized water until the leaching water presents neutral, and then dry the filter cake to obtain modified graphene oxide. Take 6 parts by weight of bisphenol A type epoxy resin E-44 and heat to 100°C, and then add 1 part by weight of modified graphene oxide and 0.1 part by weight of tetrabutylammonium bromide to mix and stir for reaction for 6 h. After the reaction is completed, naturally cool it to room temperature to obtain a modified epoxy resin material.
[0039] Preparation Example 2:
[0040] The preparation method of the modified epoxy resin material specifically includes the following processes:
[0041] The 3 parts by weight of graphene powder with particle size of 15 μm were weighed into a beaker, and then 132 parts by weight of 98% concentrated sulfuric acid was slowly poured into the beaker to mix with the graphene powder. Then the mixture was placed in a low temperature environment of 4°C. Then 30 parts by weight of potassium permanganate was slowly added into the above mixture, and stirred at a speed of 200 r / min and reacted in a low temperature environment of 4°C for 3 h. After the low temperature reaction, the mixture was taken out and placed in a temperature environment of 65°C for further stirring reaction for 2 h. After the reaction, the mixture was cooled to room temperature, and then 5% hydrogen peroxide was added to mix and stir until the system showed yellow. The particles were collected by filtration, washed with dilute hydrochloric acid first, then washed with deionized water until the pH of the washing water was neutral, and then dried to obtain graphene oxide. 2 parts by weight of graphene oxide and 7 parts by weight of maleic acid were added together into anhydrous acetone, treated by ultrasonic power of 300 W for 10 min, and then 0.12 parts by weight of p-toluenesulfonic acid was added to mix and stir, and heated to 80°C for timed reaction for 4.5 h. After the reaction, the mixture was cooled to room temperature, and then filtered to obtain a filter cake. The filter cake was repeatedly washed with deionized water until the washing water showed neutral, and then the filter cake was dried to obtain modified graphene oxide. 8 parts by weight of bisphenol A type epoxy resin E-44 was weighed and heated to 105°C, and then 1 part by weight of modified graphene oxide and 0.15 parts by weight of tetrabutylammonium bromide were added to mix and stir for reaction for 7 h. After the reaction, the mixture was naturally cooled to room temperature to obtain a modified epoxy resin material.
[0042] Preparation Example 3:
[0043] The preparation method of the modified epoxy resin material specifically includes the following processes:
[0044] The graphene powder with a particle size of 20 μm is weighed at 3 parts by weight and placed in a beaker. Concentrated sulfuric acid with a mass fraction of 98% is weighed at 138 parts by weight and slowly added to the beaker to mix with the graphene powder. Then, the mixture is placed in a low-temperature environment at 6°C. Potassium permanganate is weighed at 33 parts by weight and slowly added to the mixture. The mixture is stirred at a speed of 200 r / min and reacted in the low-temperature environment at 6°C for 4 h. After the low-temperature reaction, the mixture is taken out and continuously stirred and reacted at a temperature of 65°C for 3 h. After the reaction, the mixture is cooled to room temperature. Hydrogen peroxide with a mass fraction of 5% is added to the mixture, which is stirred until the mixture is yellow. The particles are collected by filtration. The particles are first washed with dilute hydrochloric acid, then washed with deionized water until the pH of the washing water is neutral. The particles are dried to obtain graphene oxide. Graphene oxide is weighed at 2 parts by weight and added to dehydrated acetone. Maleic acid is weighed at 8 parts by weight and added to the mixture. The mixture is treated by ultrasonic power of 300 W for 10 min. p-Toluenesulfonic acid is weighed at 0.18 parts by weight and added to the mixture. The mixture is stirred and heated to 85°C for timed reaction for 5 h. After the reaction, the mixture is cooled to room temperature. The filter cake is obtained by filtration. The filter cake is repeatedly washed with deionized water until the washing water is neutral. The filter cake is dried to obtain modified graphene oxide. Bisphenol A type epoxy resin E-51 is weighed at 10 parts by weight and heated to 105°C. Modified graphene oxide is weighed at 1 part by weight and added to the mixture. Tetrabutylammonium bromide is weighed at 0.15 parts by weight and added to the mixture. The mixture is stirred and reacted for 8 h. After the reaction, the mixture is naturally cooled to room temperature to obtain a modified epoxy resin material.
[0045] Preparation Example 4:
[0046] The method for preparing the modified epoxy resin material specifically includes the following processes:
[0047] The graphene powder with a particle size of 20 μm is weighed at 3 parts by weight and placed in a beaker. Then 144 parts by weight of concentrated sulfuric acid with a mass fraction of 98% is slowly added into the beaker to mix with the graphene powder. Subsequently, the mixture is placed in a low-temperature environment at 6°C. Then 36 parts by weight of potassium permanganate is slowly added into the above mixture. The mixture is stirred at a rotation speed of 200 r / min and reacted in the low-temperature environment at 6°C for 4 h. After the low-temperature reaction, the mixture is taken out and continuously stirred and reacted in a temperature environment at 70°C for 3 h. After the reaction, the mixture is cooled to room temperature. Then hydrogen peroxide with a mass fraction of 5% is added into the mixture to mix and stir until the mixture presents yellow. The particles are collected by filtration. The particles are first washed with dilute hydrochloric acid, then washed with deionized water until the pH of the washing water is neutral. Then the particles are dried to obtain graphene oxide. Then 2 parts by weight of the graphene oxide and 10 parts by weight of maleic acid are added into anhydrous acetone. The mixture is treated by ultrasonic power of 300 W for 10 min. Then 0.24 parts by weight of p-toluenesulfonic acid is added into the mixture to mix and stir. The mixture is heated to 90°C and reacted for 5 h. After the reaction, the mixture is cooled to room temperature. Then the filter cake is obtained by filtration. The filter cake is repeatedly washed with deionized water until the washing water presents neutral. Then the filter cake is dried to obtain modified graphene oxide. Then 12 parts by weight of bisphenol A type epoxy resin E-51 is heated to 110°C. Then 1 part by weight of the modified graphene oxide and 0.2 parts by weight of tetrabutylammonium bromide are added into the epoxy resin to mix and stir. The mixture is reacted for 8 h. After the reaction, the mixture is naturally cooled to room temperature to obtain a modified epoxy resin material.
[0048] Preparation Example 5:
[0049] The method for preparing the modified epoxy resin material specifically includes the following processes:
[0050] The 3 parts by weight of graphene powder with particle size of 20 μm were weighed into a beaker, and then 150 parts by weight of 98% concentrated sulfuric acid was slowly poured into the beaker to mix with the graphene powder. Then the mixture was placed in a low temperature environment of 6°C. Then 40 parts by weight of potassium permanganate was slowly added into the above mixture, and stirred at a speed of 200 r / min and reacted in a low temperature environment of 6°C for 5 h. After the low temperature reaction, the mixture was taken out and placed in a temperature environment of 70°C for further stirring reaction for 4 h. After the reaction, the mixture was cooled to room temperature, and then 5% hydrogen peroxide was added to mix and stir until the system showed yellow. The particles were collected by filtration, washed with dilute hydrochloric acid first, then washed with deionized water until the pH of the washing water was neutral, and then dried to obtain graphene oxide. 2 parts by weight of graphene oxide and 10 parts by weight of maleic acid were added together into anhydrous acetone, treated by ultrasonic power of 300 W for 10 min, and then 0.24 parts by weight of p-toluenesulfonic acid was added to mix and stir, and heated to 90°C for timed reaction for 5 h. After the reaction, the mixture was cooled to room temperature, and then filtered to obtain a filter cake. The filter cake was repeatedly washed with deionized water until the washing water showed neutral, and then the filter cake was dried to obtain modified graphene oxide. 12 parts by weight of bisphenol A type epoxy resin E-51 was heated to 110°C, and then 1 part by weight of modified graphene oxide and 0.2 part by weight of tetrabutylammonium bromide were added to mix and stir for reaction for 8 h. After the reaction, the mixture was naturally cooled to room temperature to obtain a modified epoxy resin material.
[0051] Preparation Example 6:
[0052] The preparation method of the modified epoxy resin material specifically includes the following processes:
[0053] Take 3 parts by weight of graphene powder with a particle size of 15 μm into a beaker, then slowly pour 115 parts by weight of concentrated sulfuric acid with a mass fraction of 98% into the beaker to mix with the graphene powder, then place it in a low-temperature environment of 4°C, then take 15 parts by weight of potassium permanganate and slowly add it to the above-mentioned mixed system, stir at a speed of 200 r / min and react in a low-temperature environment of 4°C for 3 h. After the low-temperature reaction is completed, take it out and continue to stir and react at a temperature environment of 60°C for 2 h, then cool to room temperature, add hydrogen peroxide with a mass fraction of 5% to mix and stir until the system presents yellow, then filter and collect the particles, first wash with dilute hydrochloric acid, then rinse with deionized water until the pH of the rinsing water is neutral, then dry to obtain graphene oxide; take 2 parts by weight of graphene oxide and 6 parts by weight of maleic acid together into anhydrous acetone, treat for 10 min under an ultrasonic power of 300 W, then add 0.06 parts by weight of p-toluenesulfonic acid to mix, stir and heat to 80°C for timed reaction for 4 h. After the reaction is completed, cool to room temperature, then filter to obtain a filter cake, repeatedly rinse the filter cake with deionized water until the rinsing water presents neutral, then dry the filter cake to obtain modified graphene oxide; take 6 parts by weight of bisphenol A type epoxy resin E-44 and heat to 100°C, then add 1 part by weight of modified graphene oxide and 0.1 part by weight of tetrabutylammonium bromide to mix, stir and react for 6 h. After the reaction is completed, naturally cool to room temperature to obtain a modified epoxy resin material.
[0054] Preparation Example 7:
[0055] The preparation method of the modified epoxy resin material specifically includes the following processes:
[0056] In the preparation example 4, the particle size of the graphene powder is replaced by a particle size of 50 μm, and the rest of the processes remain the same as those in the preparation example 4.
[0057] Preparation Example 8:
[0058] The preparation method of the modified epoxy resin material specifically includes the following processes:
[0059] In the preparation example 4, the particle size of the graphene powder is replaced by a particle size of 5 μm, and the rest of the processes remain the same as those in the preparation example 4.
[0060] Preparation Example 9:
[0061] The preparation method of the modified epoxy resin material specifically includes the following processes:
[0062] In the preparation example 4, the maleic acid is replaced by succinic acid, and the rest of the processes remain the same as those in the preparation example 4.
[0063] Preparation Example 10:
[0064] The preparation method of the modified epoxy resin material specifically comprises the following process:
[0065] The maleic acid in the preparation example 4 is replaced by cis, cis-2, 4-hexadienoic acid, and the rest of the process is consistent with that of the preparation example 4.
[0066] Preparation example 11:
[0067] The preparation method of the modified epoxy resin material specifically comprises the following process:
[0068] Take 3 parts by weight of graphene powder with a particle size of 20 μm into a beaker, then slowly pour 144 parts by weight of concentrated sulfuric acid with a mass fraction of 98% into the beaker to mix with the graphene powder, then place it in a low-temperature environment of 6 ℃, then take 36 parts by weight of potassium permanganate and slowly add it to the above-mentioned mixed system, stir at a speed of 200 r / min and react in a low-temperature environment of 6 ℃ for 4 h. After the low-temperature reaction is completed, take it out and place it in a temperature environment of 70 ℃ to continue stirring and reacting for 3 h. After the reaction is completed, cool it to room temperature, add 5% hydrogen peroxide with mass fraction to mix and stir until the system presents yellow, filter and collect the particles, first wash them with dilute hydrochloric acid, then wash them with deionized water until the pH of the washing water is neutral, and then dry them to obtain graphene oxide; take 12 parts by weight of bisphenol A type epoxy resin E-51 and heat it to 110 ℃, then add 1 part by weight of graphene oxide and 0.2 part by weight of tetrabutylammonium bromide to mix and stir for 8 h. After the reaction is completed, naturally cool it to room temperature to obtain a modified epoxy resin material.
[0069] Preparation example 12:
[0070] The preparation method of the modified heat-conducting filler specifically comprises the following process:
[0071] Put aluminum nitride with a particle size of 30 μm into an acetone solution and clean it with an ultrasonic power of 400 W for 20 min, then replace the acetone with deionized water and clean it with an ultrasonic power of 400 W for 20 min, and then dry it at 50 ℃ to remove water. Put the cleaned aluminum nitride into the reaction chamber of a plasma reactor, then introduce oxygen into the reaction chamber to discharge the air in the reaction chamber, control the flow rate of the oxygen to be 100 mL / min, turn on the power to discharge, control the discharge power to be 200 W, make the reaction chamber appear a discharge point phenomenon, and then start the timing process for 60 s. After the process is completed, mix and disperse 10 parts by weight of modified aluminum nitride, 4 parts by weight of vinyltrimethoxysilane, 30 parts by weight of deionized water and 100 parts by weight of anhydrous ethanol together in an ultrasonic power of 200 W for 30 min to form a dispersion liquid, adjust the pH of the dispersion liquid to 4 with dilute hydrochloric acid, and then heat it to 70 ℃ to react for 60 min. After the reaction is completed, centrifugally separate the obtained precipitate and place it in an oven at 60 ℃ to dry to obtain a modified heat-conducting filler.
[0072] Preparation Example 13
[0073] The preparation method of the modified thermally conductive filler specifically includes the following processes:
[0074] The aluminum nitride with a particle size of 30 μm was placed in an acetone solution and cleaned for 20 min at an ultrasonic power of 400 W, then the acetone was replaced with deionized water and cleaned for 20 min at an ultrasonic power of 400 W, and then dried at 50°C to remove the water. The cleaned aluminum nitride was placed in the reaction chamber of a plasma reactor, then oxygen was introduced into the reaction chamber to discharge the air in the reaction chamber, the flow rate of the oxygen was controlled to be 120 mL / min, the power was turned on to discharge, the discharge power was controlled to be 200 W, the reaction chamber was made to have a discharge point phenomenon, and then the timing processing was started for 70 s. After the processing was completed, 10 parts by weight of the modified aluminum nitride, 5 parts by weight of vinyltrimethoxysilane, 40 parts by weight of deionized water, and 120 parts by weight of anhydrous ethanol were mixed and dispersed together in an ultrasonic power of 200 W for 30 min to form a dispersion liquid, the pH of the dispersion liquid was adjusted to 4 with dilute hydrochloric acid, and then heated to 70°C for reaction for 65 min. After the reaction was completed, the obtained precipitate was separated by centrifugation and dried in an oven at 60°C to obtain the modified thermally conductive filler.
[0075] Preparation Example 14
[0076] The preparation method of the modified thermally conductive filler specifically includes the following processes:
[0077] The aluminum nitride with a particle size of 40 μm was placed in an acetone solution and cleaned for 20 min at an ultrasonic power of 400 W, then the acetone was replaced with deionized water and cleaned for 20 min at an ultrasonic power of 400 W, and then dried at 50°C to remove the water. The cleaned aluminum nitride was placed in the reaction chamber of a plasma reactor, then oxygen was introduced into the reaction chamber to discharge the air in the reaction chamber, the flow rate of the oxygen was controlled to be 140 mL / min, the power was turned on to discharge, the discharge power was controlled to be 300 W, the reaction chamber was made to have a discharge point phenomenon, and then the timing processing was started for 80 s. After the processing was completed, 10 parts by weight of the modified aluminum nitride, 6 parts by weight of vinyltriethoxysilane, 50 parts by weight of deionized water, and 140 parts by weight of anhydrous ethanol were mixed and dispersed together in an ultrasonic power of 200 W for 30 min to form a dispersion liquid, the pH of the dispersion liquid was adjusted to 4.5 with dilute hydrochloric acid, and then heated to 80°C for reaction for 65 min. After the reaction was completed, the obtained precipitate was separated by centrifugation and dried in an oven at 60°C to obtain the modified thermally conductive filler.
[0078] Preparation Example 15
[0079] The preparation method of the modified thermally conductive filler specifically includes the following processes:
[0080] The aluminum nitride with a particle size of 40 μm was put into an acetone solution and cleaned for 20 min at an ultrasonic power of 400 W, then the acetone was replaced with deionized water and cleaned for 20 min at an ultrasonic power of 400 W, and then dried at 50°C to remove the water. The cleaned aluminum nitride was put into the reaction chamber of a plasma reactor, then oxygen was introduced into the reaction chamber to discharge the air in the reaction chamber, the flow rate of the oxygen was controlled to be 150 mL / min, the power was turned on to discharge, the discharge power was controlled to be 300 W, the reaction chamber was made to have a discharge point, and then the timing was started for 90 s. After the treatment was completed, 10 parts by weight of the modified aluminum nitride, 7 parts by weight of vinyltriethoxysilane, 60 parts by weight of deionized water, and 150 parts by weight of anhydrous ethanol were mixed and dispersed together in an ultrasonic power of 200 W for 30 min to form a dispersion liquid, the pH of the dispersion liquid was adjusted to 4.5 with dilute hydrochloric acid, and then heated to 80°C for reaction for 70 min. After the reaction was completed, the obtained precipitate was separated by centrifugation and dried in an oven at 60°C to obtain the modified heat-conductive filler.
[0081] Preparation Example 16:
[0082] The preparation method of the modified heat-conductive filler specifically includes the following processes:
[0083] The aluminum nitride with a particle size of 40 μm in Preparation Example 14 was replaced with aluminum nitride with a particle size of 70 μm, and the other conditions were the same as those in Preparation Example 14.
[0084] Preparation Example 17:
[0085] The preparation method of the modified heat-conductive filler specifically includes the following processes:
[0086] The vinyltriethoxysilane in Preparation Example 14 was replaced with γ-aminopropyltriethoxysilane, and the other conditions were the same as those in Preparation Example 14.
[0087] Preparation Example 18:
[0088] The preparation method of the modified heat-conductive filler specifically includes the following processes:
[0089] The vinyltriethoxysilane in Preparation Example 14 was replaced with N-phenyl-3-aminopropyltrimethoxysilane, and the other conditions were the same as those in Preparation Example 14.
[0090] Preparation Example 19:
[0091] The preparation method of the modified heat-conductive filler specifically includes the following processes:
[0092] The aluminum nitride with a particle size of 40 μm is put into an acetone solution and cleaned for 20 min under an ultrasonic power of 400 W, then the acetone is replaced by deionized water and cleaned for 20 min under an ultrasonic power of 400 W, and then dried at 50 ℃ to remove water. The cleaned aluminum nitride is put into the reaction chamber of a plasma reactor, then oxygen is introduced into the reaction chamber to discharge the air in the reaction chamber, the flow rate of the oxygen is controlled to be 150 mL / min, the power is turned on to discharge, the discharge power is controlled to be 300 W, the reaction chamber is made to have a discharge point phenomenon, and then the time processing is started for 90 s to obtain the modified aluminum nitride directly as a modified heat-conducting filler.
[0093] Example 1:
[0094] A graphene-modified epoxy resin-based packaging material and a preparation method thereof, specifically comprising the following processes:
[0095] The modified epoxy resin material obtained in Preparation Example 1, 16 parts by weight of tetrahydrophthalic anhydride, 1 part by weight of a curing accelerator triethylamine, 0.4 parts by weight of benzoyl peroxide, and 25 parts by weight of the modified heat-conducting filler obtained in Preparation Example 12 are mixed and mechanically stirred and dispersed for 30 min to obtain a dispersion, the dispersion is poured into a mold coated with a microcrystalline wax release agent, then the mold is vacuumized in a vacuum box at 45 ℃ for 30 min to remove the bubbles in the dispersion, then the mold is cured at 110 ℃ for 1 h, and then cured at 130 ℃ for 2 h, and then cooled to room temperature to be demolded to obtain an epoxy resin-based packaging material.
[0096] Example 2:
[0097] A graphene-modified epoxy resin-based packaging material and a preparation method thereof, specifically comprising the following processes:
[0098] The modified epoxy resin material obtained in Preparation Example 2, 17 parts by weight of tetrahydrophthalic anhydride, 1.5 parts by weight of a curing accelerator triethylamine, 0.4 parts by weight of benzoyl peroxide, and 26 parts by weight of the modified heat-conducting filler obtained in Preparation Example 13 are mixed and mechanically stirred and dispersed for 30 min to obtain a dispersion, the dispersion is poured into a mold coated with a microcrystalline wax release agent, then the mold is vacuumized in a vacuum box at 45 ℃ for 30 min to remove the bubbles in the dispersion, then the mold is cured at 110 ℃ for 1 h, and then cured at 130 ℃ for 2 h, and then cooled to room temperature to be demolded to obtain an epoxy resin-based packaging material.
[0099] Example 3:
[0100] A graphene-modified epoxy resin-based packaging material and a preparation method thereof, specifically comprising the following processes:
[0101] Take 28 parts by weight of the modified epoxy resin material obtained in Preparation Example 3, 18 parts by weight of isophorone diamine, 1.5 parts by weight of curing accelerator triethanolamine, 0.5 parts by weight of benzoyl peroxide and 27 parts by weight of the modified thermally conductive filler obtained in Preparation Example 14, mix and mechanically stir for 30 min to obtain a dispersion, pour the dispersion into a mold coated with microcrystalline wax release agent, then vacuum treatment in a vacuum box at 45℃ for 35 min to remove the bubbles in the dispersion, then first cured at 110℃ for 2h, then cured at 130℃ for 3h, and then cooled to room temperature to remove the mold to obtain an epoxy resin-based packaging material.
[0102] Example 4:
[0103] A graphene-modified epoxy resin-based packaging material and a preparation method thereof, specifically comprising the following processes:
[0104] Take 30 parts by weight of the modified epoxy resin material obtained in Preparation Example 4, 19 parts by weight of isophorone diamine, 2 parts by weight of curing accelerator 2-methylimidazole, 0.6 parts by weight of benzoyl peroxide and 28 parts by weight of the modified thermally conductive filler obtained in Preparation Example 15, mix and mechanically stir for 30 min to obtain a dispersion, pour the dispersion into a mold coated with microcrystalline wax release agent, then vacuum treatment in a vacuum box at 45℃ for 35 min to remove the bubbles in the dispersion, then first cured at 110℃ for 2h, then cured at 130℃ for 3h, and then cooled to room temperature to remove the mold to obtain an epoxy resin-based packaging material.
[0105] Comparative Example 1:
[0106] A graphene-modified epoxy resin-based packaging material and a preparation method thereof, specifically comprising the following processes:
[0107] Replace the modified epoxy resin material in Example 4 with the modified epoxy resin material obtained in Preparation Example 5, and the rest of the conditions remain the same as in Example 4.
[0108] Comparative Example 2:
[0109] A graphene-modified epoxy resin-based packaging material and a preparation method thereof, specifically comprising the following processes:
[0110] Replace the modified epoxy resin material in Example 4 with the modified epoxy resin material obtained in Preparation Example 6, and the rest of the conditions remain the same as in Example 4.
[0111] Comparative Example 3:
[0112] A graphene-modified epoxy resin-based packaging material and a preparation method thereof, specifically comprising the following processes:
[0113] The modified epoxy resin material in Example 4 is replaced with the modified epoxy resin material obtained in Preparation Example 7, and the rest of the conditions remain the same as in Example 4.
[0114] Comparative Example 4:
[0115] A graphene-modified epoxy resin-based packaging material and a preparation method thereof, specifically comprising the following processes:
[0116] The modified epoxy resin material in Example 4 is replaced with the modified epoxy resin material obtained in Preparation Example 8, and the rest of the conditions remain the same as in Example 4.
[0117] Comparative Example 5:
[0118] A graphene-modified epoxy resin-based packaging material and a preparation method thereof, specifically comprising the following processes:
[0119] The modified epoxy resin material in Example 4 is replaced with the modified epoxy resin material obtained in Preparation Example 9, and the rest of the conditions remain the same as in Example 4.
[0120] Comparative Example 6:
[0121] A graphene-modified epoxy resin-based packaging material and a preparation method thereof, specifically comprising the following processes:
[0122] The modified epoxy resin material in Example 4 is replaced with the modified epoxy resin material obtained in Preparation Example 10, and the rest of the conditions remain the same as in Example 4.
[0123] Comparative Example 7:
[0124] A graphene-modified epoxy resin-based packaging material and a preparation method thereof, specifically comprising the following processes:
[0125] The modified epoxy resin material in Example 4 is replaced with the modified epoxy resin material obtained in Preparation Example 11, and the rest of the conditions remain the same as in Example 4.
[0126] Comparative Example 8:
[0127] A graphene-modified epoxy resin-based packaging material and a preparation method thereof, specifically comprising the following processes:
[0128] The modified heat-conducting filler in Example 4 is replaced with the modified heat-conducting filler obtained in Preparation Example 16, and the rest of the conditions remain the same as in Example 4.
[0129] Comparative Example 9:
[0130] A graphene-modified epoxy resin-based packaging material and a preparation method thereof, specifically comprising the following processes:
[0131] The modified heat conductive filler in Example 4 is replaced with the modified heat conductive filler obtained in Preparation Example 17, and the rest of the conditions remain the same as in Example 4.
[0132] Comparative Example 10:
[0133] A graphene-modified epoxy resin-based packaging material and a preparation method thereof, specifically comprising the following processes:
[0134] The modified heat conductive filler in Example 4 is replaced with the modified heat conductive filler obtained in Preparation Example 18, and the rest of the conditions remain the same as in Example 4.
[0135] Comparative Example 11:
[0136] A graphene-modified epoxy resin-based packaging material and a preparation method thereof, specifically comprising the following processes:
[0137] The modified heat conductive filler in Example 4 is replaced with the modified heat conductive filler obtained in Preparation Example 19, and the rest of the conditions remain the same as in Example 4.
[0138] Comparative Example 12:
[0139] A graphene-modified epoxy resin-based packaging material and a preparation method thereof, specifically comprising the following processes:
[0140] The isophorone diamine in Example 4 is replaced with phthalic anhydride, and the rest of the conditions remain the same as in Example 4.
[0141] Comparative Example 13:
[0142] A graphene-modified epoxy resin-based packaging material and a preparation method thereof, specifically comprising the following processes:
[0143] 30 parts by weight of the modified epoxy resin material obtained in Preparation Example 4, 19 parts by weight of isophorone diamine, 2 parts by weight of a curing accelerator 2-methylimidazole, 0.6 parts by weight of benzoyl peroxide, and 40 parts by weight of the modified heat conductive filler obtained in Preparation Example 15 are mixed and mechanically stirred and dispersed for 30 min to obtain a dispersion, the dispersion is poured into a mold coated with a microcrystalline wax release agent, then vacuum treatment is performed in a vacuum box at 45°C for 35 min to remove the gas bubbles in the dispersion, and then the dispersion is cured at 110°C for 2 h, then cured at 130°C for 3 h, and then cooled to room temperature to remove the mold to obtain an epoxy resin-based packaging material.
[0144] Comparative Example 14:
[0145] A graphene-modified epoxy resin-based packaging material and a preparation method thereof, specifically comprising the following processes:
[0146] The modified epoxy resin material obtained in Preparation Example 4, 19 parts by weight of isophorone diamine, 2 parts by weight of curing accelerator 2-methylimidazole, 0.6 parts by weight of benzoyl peroxide and 28 parts by weight of the modified heat-conductive filler obtained in Preparation Example 15 were weighed and mixed and mechanically stirred for 30 min to obtain a dispersion, the dispersion was poured into a mold coated with microcrystalline wax release agent, then the dispersion was treated in a vacuum box at 60°C for 50 min to remove the bubbles in the dispersion, then cured at 110°C for 2 h, then cured at 130°C for 3 h and cooled to room temperature to remove the mold to obtain an epoxy resin-based packaging material.
[0147] According to GB / T 29313-2012 Test Method for Thermal Conductivity of Electrical Insulating Materials, the thermal conductivity of the epoxy resin-based packaging materials obtained in Examples 1-4 and Comparative Examples 1-14 was tested, and the results are shown in Table 1 below.
[0148] Table 1 Thermal conductivity test results
[0149]
[0150]
[0151] According to GB / T 1843-2008 Determination of Izod Impact Strength of Plastics, the impact strength of the epoxy resin-based packaging materials obtained in Examples 1-4 and Comparative Examples 1-14 was tested, the sample size was 80 mm x 10 mm x 4 mm, and the notch was 2 mm, and the results are shown in Table 2 below.
[0152] Table 2 Impact strength test results
[0153]
[0154]
[0155] According to GB / T 1410-2006 Test Method for Volume Resistivity and Surface Resistivity of Solid Insulating Materials, the volume resistivity of the epoxy resin-based packaging materials obtained in Examples 1-4 and Comparative Examples 1-14 was measured, and the results are shown in Table 3 below.
[0156] Table 3 Volume resistivity test results
[0157]
[0158]
[0159] From the above Tables 1-3, the following conclusions can be drawn:
[0160] (1) Through Examples 1-4, it can be found that the epoxy resin-based packaging material obtained by modifying the epoxy resin and the thermally conductive filler respectively and then curing has good thermal conductivity, impact resistance and insulation performance.
[0161] (2) Through Comparative Examples 1 and 2, it can be found that although the oxidation of graphene helps subsequent surface modification and weakens the electrical conductivity of graphene, in the present system, the oxidation is too strong, although it can further improve the insulation performance, but it may cause the graphene structure to be excessively damaged, and may enhance the hydrogen bonding and chemical bonding between graphene and epoxy resin, which may make the accumulation more compact, not only not conducive to the improvement of the thermal conductivity of the prepared epoxy resin-based packaging material, but also may cause the formation of a brittle interface due to excessive accumulation, resulting in a decrease in impact strength, which is not conducive to use; and if the oxidation degree is too low, the graphene sp 2 The hexagonal honeycomb formed by hybridization retains more, has strong electrical conductivity, poor insulation performance, and the oxidation degree is too low, which may result in poor modification of graphene, poor interface compatibility with epoxy resin, and easy to cause interface pores to weaken the thermal conductivity and impact strength.
[0162] (3) Through Comparative Examples 3 and 4, it can be found that in the present system, if the particle size of the graphene powder used is too large, the thermal conductivity and impact strength will be poor, which may be because although the large-size graphene powder is more likely to form a continuous thermal conduction network to improve the thermal conductivity, but the surface modification of graphene in the preparation conditions in the present system is poor, which may still be more likely to cause the thermal conductivity of the epoxy resin-based packaging material to be weakened due to agglomeration, and the large-size graphene may cause the material to be too brittle, the impact strength to be reduced, and the large-size graphene powder may result in poor insulation performance of the prepared epoxy resin-based packaging material; and in the present system, if the particle size of the graphene powder used is too small, the oxidation may be too strong in the system, which may cause the graphene structure to be excessively damaged, and may enhance the hydrogen bonding and chemical bonding between graphene and epoxy resin, which may make the accumulation more compact, not conducive to the improvement of the thermal conductivity and impact strength of the prepared epoxy resin-based packaging material.
[0163] (4) Through Comparative Example 5, it can be found that although succinic acid also has double carboxyl groups, it may lack covalent bonding between the double bonds of the modified epoxy resin material and the modified thermally conductive filler, which may result in poor interface bonding between the modified thermally conductive filler and the modified epoxy resin material, and the prepared epoxy resin-based packaging material has poor thermal conductivity and impact strength, and poor insulation performance.
[0164] (5) It can be found from Comparative Example 6 that although cis, cis-2,4-hexadienedioic acid has double carboxyl groups and carbon-carbon unsaturated double bonds, the interface bonding between the modified graphene oxide and the epoxy resin is weakened due to the too long carbon chain, which may lead to uneven dispersion, and thus the prepared epoxy resin-based packaging material has poor thermal conductivity and impact strength.
[0165] (6) It can be found from Comparative Example 7 that the prepared epoxy resin-based packaging material has poor thermal conductivity and impact strength when the modified graphene oxide is directly used for mixing reaction with the epoxy resin, which may be due to the poor interface bonding between the graphene oxide and the epoxy resin in the system, and the modification of the modified thermal conductive filler cannot achieve good thermal conductivity modification.
[0166] (7) It can be found from Comparative Example 8 that when the particle size of aluminum nitride is further increased, the prepared epoxy resin-based packaging material has poor thermal conductivity and impact strength, which may be due to the fact that although large particle size is helpful to form a continuous thermal conduction path, in the system, the effect of plasma oxidation modification on large particle size aluminum nitride is poor, which may lead to easy agglomeration and formation of pores, affecting the thermal conductivity and increasing the brittleness of the epoxy resin-based packaging material.
[0167] (8) It can be found from Comparative Example 9 that although γ-aminopropyl triethoxysilane also has coupling effect, it does not contain unsaturated carbon-carbon double bonds, which may lead to poor covalent bonding between the modified epoxy resin material and the modified thermal conductive filler, and thus the interface bonding between the modified thermal conductive filler and the modified epoxy resin material is poor, the prepared epoxy resin-based packaging material has poor thermal conductivity and impact strength, and the insulation performance is poor.
[0168] (9) It can be found from Comparative Example 10 that although N-phenyl-3-aminopropyl trimethoxysilane has coupling effect due to the unsaturation of the benzene ring, on the one hand it does not contain unsaturated carbon-carbon double bonds, and on the other hand the rigid structure of the benzene ring may lead to too strong rigidity and too large brittleness of the prepared epoxy resin-based packaging material, and both factors lead to poor thermal conductivity and impact strength of the epoxy resin-based packaging material, and the insulation performance is poor.
[0169] (10) It can be found from Comparative Example 11 that the thermal conductivity and impact strength of the epoxy resin-based packaging material prepared by directly using the heat-conducting filler aluminum nitride after plasma treatment are poor, and the insulation performance is also poor, which may be due to the fact that the modified aluminum nitride after plasma treatment is not subjected to post-treatment of group modification in the system, the interface bonding between the modified epoxy resin and the modified heat-conducting filler may still be poor, and only relying on the modified epoxy resin cannot achieve good thermal conductivity modification, and the insulation performance cannot be improved well.
[0170] (11) It can be found from Comparative Example 12 that although phthalic anhydride is a commonly used curing agent for epoxy resin, in the system, due to the rigid benzene ring structure and steric hindrance of phthalic anhydride, if a curing agent containing a rigid benzene ring is used after modification of the epoxy resin and the heat-conducting filler aluminum nitride, the modified heat-conducting filler and the modified epoxy resin material may be unevenly mixed and dispersed, the interface bonding is poor, and then the epoxy resin-based packaging material may be prone to poor thermal conductivity and impact strength due to excessive rigidity and brittleness.
[0171] (12) It can be found from Comparative Example 13 that when the amount of the modified heat-conducting filler is further increased, although the insulation performance remains good, the thermal conductivity and impact resistance performance are poor, which may be due to the fact that although the aluminum nitride is modified to synergistically improve the modified epoxy resin material, when the amount exceeds a certain value, the interface bonding may have defects, and the modification effect of the system may not be sufficient to support further increasing the thermal conductivity of the epoxy resin-based packaging material by increasing the amount.
[0172] (13) It can be found from Comparative Example 14 that when the temperature and time of vacuum degassing are further increased, the initiation catalysis of benzoyl peroxide may be activated in advance due to high temperature, leading to premature condensation polymerization of the modified epoxy resin material and the modified heat-conducting filler, which may lead to uneven mixing between materials and poor crosslinking, and on the contrary, the thermal conductivity and impact strength of the epoxy resin-based packaging material are poor.
[0173] The above embodiments have described the technical solutions and beneficial effects of the present application in detail. It should be understood that the above description is only a specific embodiment of the present application and is not intended to limit the present application. Without departing from the spirit and scope of the present application, various changes and improvements can be made to the present application, and these changes and improvements all fall within the scope of the claimed present application.
Claims
1. A method for preparing a graphene-modified epoxy resin-based encapsulant material, characterized by, The preparation method comprises the following steps: The modified epoxy resin material, the curing agent, the curing accelerator, the benzoyl peroxide and the modified heat-conductive filler are mixed and dispersed to form a dispersion material in a weight ratio of 20-30:16-19:1-2:0.4-0.6:25-28, the dispersion material is poured into a mold coated with a release agent, and after vacuum degassing treatment at 45 DEG C for 30-35 min, the epoxy resin-based packaging material is obtained by sequentially curing at 110 DEG C for 1-2 h and curing at 130 DEG C for 2-3 h; The preparation method of the modified epoxy resin material comprises the following steps: The graphene powder, concentrated sulfuric acid and potassium permanganate are mixed and reacted at 4 DEG C-6 DEG C for 3 h-4 h, and then the temperature is increased to 60 DEG C-70 DEG C for reaction for 2 h-3 h to obtain graphene oxide; The graphene oxide, enoic acid and p-toluenesulfonic acid are mixed and heated to 80 DEG C-90 DEG C for reaction for 4 h-5 h to obtain modified graphene oxide; The modified graphene oxide, epoxy resin and tetrabutylammonium bromide are mixed and stirred and heated to 100 DEG C-110 DEG C for reaction for 6 h-8 h to obtain the modified epoxy resin material; The enoic acid comprises maleic acid; The preparation method of the modified heat-conductive filler comprises the following steps: The modified aluminum nitride is obtained by plasma oxidation of aluminum nitride; The modified aluminum nitride, unsaturated silane coupling agent, deionized water and anhydrous ethanol are mixed in a weight ratio of 1:0.4-0.7:3-6:10-15 to form a dispersion liquid, the pH of the dispersion liquid is adjusted to 4-4.5 and heated to 70 DEG C-80 DEG C for reaction for 60 min-70 min to obtain the modified heat-conductive filler.
2. The method for preparing a graphene-modified epoxy resin-based encapsulation material according to claim 1, characterized in that, The weight ratio of the graphene powder:concentrated sulfuric acid:potassium permanganate is 1:42-48:9-12.
3. The method for preparing a graphene-modified epoxy resin-based encapsulation material according to claim 1, characterized in that, The weight ratio of the graphene oxide:enoic acid:p-toluenesulfonic acid is 1:3-5:0.03-0.
12.
4. The method for preparing a graphene-modified epoxy resin-based encapsulation material according to claim 1, characterized in that, The weight ratio of the modified graphene oxide:epoxy resin:tetrabutylammonium bromide is 1:6-12:0.1-0.
2.
5. The method for preparing a graphene-modified epoxy resin-based encapsulation material according to claim 1, characterized in that, The conditions of the plasma oxidation include that the plasma gas source is oxygen, the gas flow is 100 mL / min-150 mL / min, the treatment power is 200 W-300 W and the treatment time is 60 s-90 s.
6. The method of claim 1, wherein the graphene-modified epoxy resin-based encapsulant is prepared by the steps of: mixing graphene oxide and an epoxy resin to form a mixture; adding a reducing agent to the mixture to reduce the graphene oxide to graphene; and adding a curing agent to the mixture to cure the graphene-modified epoxy resin-based encapsulant. The unsaturated silane coupling agent comprises vinyltrimethoxysilane or vinyltriethoxysilane. 7.An epoxy resin-based packaging material prepared by the preparation method of the graphene-modified epoxy resin-based packaging material according to any one of claims 1-6.
Citation Information
Patent Citations
Preparation method of ultrahigh thermal conductivity epoxy resin / graphene composite material
CN110804280A
Graphene modified resin packaging material and preparation method thereof
CN111533486A
Graphene oxide modified polypropylene-based square corrugated pipe and manufacturing method thereof
CN111607168A